PENGGUNAAN BENFORD'S LAW UNTUK MENENTUKAN PRIORITAS AUDIT PAJAK PERTAMBAHAN NILAI - Prasetyo, Kristian Agung; Djufri, Muhammad (Scientax, 2020)
Value Added Tax has contributed significantly in Indonesia’s tax revenue and continually to progress in the term of its role in increasing the tax revenue. Unfortunately, the phenomenon of VAT fraud, intended to minimize VAT payment, would give consequences in violating the tax revenue. In order to minimize this phenomenon, DGT has been maximizing the use of technology in VAT administration. Since the 1st of July 2016, the use of e-Faktur has been enforced to all registered Taxable Entrepreneurs. The enforcement of the e-Faktur has been effectively reducing the number of counterfeit tax invoices. Nonetheless, the e-Faktur is still not be able to capture the accuracy of transactions in Tax Invoices. As a result, DGT relies heavily on the approach of conventional audit for auditing taxpayers’ VAT compliance. This approach is considered to be less effective and become a problem since DGT does not have sufficient tax auditors. The number of tax invoices that needs to be audited could be piled up whilst the amount of tax credits to be audited are also high. This paper aims to discuss this problem by using a statistical technique namely Benford's law. It is recognized in the forensic audit literature that Benford's law can be a tool to help an early fraud examination of many transactions. By using particular statistical procedures, this paper will argue that Benford's Law can be used to analyze the accuracy of VAT value on tax invoices that is reported on the monthly VAT Return.